2017
DOI: 10.1097/id.0000000000000615
|View full text |Cite
|
Sign up to set email alerts
|

Standard Drilling Versus Ultrasonic Implant Site Preparation

Abstract: Implant placement after ultrasonic preparation can be considered a predictable technique leading to clinical and biological responses similar to SD 4 weeks after insertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…In the present work, overall mean IT value was 82.3 Ncm, with a relatively high mean value of 55.2 Ncm in soft D4 bone, when compared to others studies with ISQ values ranging between 22 Ncm and 40 Ncm when using implants with tapered geometry [9,11]. Low implant IT was reported to favor micromotion [35], potentially jeopardizing implant osseointegration [36].…”
Section: Discussionmentioning
confidence: 44%
See 3 more Smart Citations
“…In the present work, overall mean IT value was 82.3 Ncm, with a relatively high mean value of 55.2 Ncm in soft D4 bone, when compared to others studies with ISQ values ranging between 22 Ncm and 40 Ncm when using implants with tapered geometry [9,11]. Low implant IT was reported to favor micromotion [35], potentially jeopardizing implant osseointegration [36].…”
Section: Discussionmentioning
confidence: 44%
“…When recorded in soft and hard bone, mean ISQ values showed significantly different results (73.2 and 81.9, respectively). The correlation between ISQ values and bone density was already reported in the literature with higher values in denser bone qualities [10,11]. Nevertheless, the relationship between IT and ISQ was not linear: They correlated significantly only in soft bone (D4, p = 0.0008), while the strength of their association was not significant in the other groups (D1, p = 0.28; D2, p = 0.31; D3, p = 0.16).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…UISP was previously clinically tested on a large number of patients showing that this novel approach could represent a reliable alternative to traditional drilling protocols [ 37 , 38 ]. Recent studies showed that UISP leads to a limited decrease of primary stability during the early phases of bone healing [ 32 34 ], likely due to a slightly different biochemical response in the osteotomy area.…”
Section: Discussionmentioning
confidence: 99%